Fracture risks among patients with atrial fibrillation receiving different oral anticoagulants: a real-world nationwide cohort study. (1st February 2020) - Huang, Huei-Kai; Liu, Peter Pin-Sung; Hsu, Jin-Yi; Lin, Shu-Man; Peng, Carol Chiung-Hui; Wang, Jen-Hung; Loh, Ching-Hui
Abstract: Aims: To evaluate the fracture risk among patients with atrial fibrillation (AF) treated with non-vitamin K antagonist oral anticoagulants (NOACs) or warfarin. Methods and results: We conducted a real-world nationwide retrospective cohort study using Taiwan's National Health Insurance Research Database. All adult patients in Taiwan newly diagnosed with AF between 2012 and 2016 who received NOACs or warfarin were enrolled and followed up until 2017. Patients treated with NOACs were sub-grouped according to the NOAC used (dabigatran, rivaroxaban, and apixaban). Propensity score matching was performed for each head-to-head comparison. Cox regression analysis, with a shared frailty model, was used to calculate the adjusted hazard ratios (aHRs) for hip, vertebral, and humerus/forearm/wrist fractures. After matching, 19 414 patients were included (9707 in each NOAC and warfarin groups). The median follow-up time was 2.4 years. Compared with warfarin, NOACs were associated with a reduced fracture risk [aHR = 0.84, 95% confidence interval (CI) = 0.77–0.93; P < 0.001]. Sub-analyses revealed that each NOAC, namely dabigatran (aHR = 0.88, 95% CI = 0.78–0.99; P = 0.027), rivaroxaban (aHR = 0.81, 95% CI = 0.72–0.90; P < 0.001), and apixaban (aHR = 0.67, 95% CI = 0.52–0.87; P = 0.003), had a reduced fracture risk. Analyses including all eligible patients, without propensity score matching, generated similar results. Conclusion: Compared with warfarin, NOAC was associated with a reduced fracture risk among AF patients. Therefore, if oral anticoagulants are indicated, NOACs rather than warfarin should be considered to lower the risk of fractures. However, further studies are needed to investigate the underlying mechanisms and elucidate causality.